"His bachelor house": The unhomely home of the fin de siècle's bourgeois bachelor in Robert Louis Stevenson's Strange Case of Dr Jekyll and Mr Hyde - Prosser, Ashleigh (2014)
This article seeks to specifically examine the ways in which the figure of the bourgeois bachelor and his construction of an alternative form of masculine domesticity in Victorian fin-de-siècle society are conveyed in Stevenson’s Gothic novella via the unhomely home space. By applying Freud’s theory of 'das unheimliche' (the uncanny, literally translated as ‘unhomely’) to a close reading of the text, this paper seeks to identify moments of the unhomely within the home and read them as spaces through which the bourgeois bachelor’s alternative form of masculine domesticity at the fin-de-siècle can be understood. This interpretation of Stevenson’s text is founded on reading the unhomely home as a literary chronotope, a symbolic representation of the experience of masculine domesticity within a specific moment in time, the Victorian fin de siècle, through a specific space, the bourgeois bachelor’s home.